(untitled) (The Pakistan Development Review, 1986)
It can hardly be denied that since the late Sixties, the introduction of High Yielding Varieties (HYVs) of a number of commodities, along with tube well irrigation and chemical fertilizers, has significantly improved the overall agricultural productivity in Pakistan [12; 15]. However what is still being debated is the effect of this phenomenon, generally termed "Green Revolution", on rural income distribution in a country where ownership and control of productive resources are far from evenly distributed. I Studies by Khan [13] and Chaudhry (7] in particular have generated a great deal of interest in this subject because of their conflicting conclusions. Khan, on the basis of his study of the Punjab and Sind, concludes that the Green Revolution, while generally being beneficial, did not benefit the small farmer as much as it did the large farmer? As a result, it led to a widening of inter-farm and inter-regional income inequalities. According to him, new varieties, which were relatively more profitable, were adopted more widely by large farmers than by the small ones. Similarly, compared with small farmers, large farmers had greater access to, and control of, modern inputs, institutional credit and tractorized farm power; enabling them to gain still more from the new technologies.